ANALISIS KERUSAKAN PRASARANA FISIK BERDASARKAN KEMIRINGAN DI PADA DAERAH IRIGASI CIRADEN UPTD WILAYAH I KABUPATEN CIANJUR - Mukhlis, Saepul; ., Tahadjuddin; Robial, Siti Muawanah (Peneliti.net, 2026)
Abstract Irrigation Area is an area that receives water from an irrigation network, physical infrastructure has a significant impact on an irrigation network, therefore the condition of the physical infrastructure in the irrigation network must be analyzed to determine the level of damage. Based on this, damage will cause problems. Based on this, researchers conducted an analysis of the damage to the physical infrastructure of the irrigation network based on the level of slope. The purpose of this study was to determine the level of damage at each slope. This study will trace the irrigation network from upstream to downstream in the Ciraden Irrigation Area located in Cianjur District, UPTD Region I, Cianjur Regency. The results of the analysis of the level of damage conditions on slopes on flat slopes there are 2 points of damage, sloping 6 damage, slightly steep 9 points of damage, and steep 8 points of damage from a total of 102 buildings and channels. So the value of damage that occurs on slopes in the Ciraden irrigation network is on a flat slope of 1.96%, a gentle slope of 5.88%, a slightly steep slope of 8.82, and on a steep slope of 7.84%. Level of Damage Condition; Physical Infrastructure; Slope